Analisis Regresi Linier Sederhana mengenai Pengaruh Toxic Masculinity terhadap Depresi pada Mahasiswa - Simanungkalit, Rebecca Gabriela; Hardjo, Suryani (Universitas Medan Area, 2025)
This study aims to empirically examine and determine the effect of toxic masculinity on depression in university students. The population of this research consisted of 57 male students from the 2020 batch of the Faculty of Psychology, Medan Area University, with a sample of 47 individuals selected using a purposive sampling technique. Simple linear regression was employed as the data analysis method. The analysis results indicate a significant influence of toxic masculinity on depression in students, with a Coefficient of Determination (R2) of 0.261 and a significance value of p = 0.001 0.050. This confirms the hypothesis that higher toxic masculinity leads to higher depression, and conversely, lower toxic masculinity leads to lower depression experienced by students. Toxic masculinity contributes 26.1% to the depression felt by students. Furthermore, the study reveals that both toxic masculinity and depression among students are categorized as high, as evidenced by the empirical mean value of toxic masculinity (16.19) being greater than the hypothetical mean (9.5), and the empirical mean value of depression (39.68) being greater than the hypothetical mean (28.5).